Peran Generasi Z dalam Simulasi Pengelolaan Limbah Program Makan Bergizi Gratis di Kota Samarinda - Annisa Camila Putri; pipit afrianti; Rasti Ananda Sihotang; Azra Belfa Nayara (HK Publishing, 2025)
Waste management remains a major challenge in Indonesia, particularly in urban areas such as Samarinda, which continues to experience increasing waste volume alongside rapid population growth and social–economic activities. One emerging source of organic waste originates from the government’s free lunch program aimed at improving children’s nutritional intake. Although this program provides significant benefits for child nutrition, it also generates a considerable amount of food residue and organic waste that can contribute to environmental pollution if not properly managed. This study aims to explore the role of Generation Z (Gen Z) in utilizing biopore technology as an alternative and eco-friendly solution for managing organic waste generated from the free lunch program. The research employs a descriptive qualitative approach through literature review, documentation, and case analysis in Samarinda City. Data were analyzed qualitatively through literature interpretation and observation of waste management practices in the field. The findings reveal that the application of biopore technology significantly reduces the volume of organic waste while producing compost beneficial for school greening and urban gardens. Moreover, this technology enhances groundwater absorption and contributes to flood mitigation in densely populated areas. The involvement of Gen Z—characterized by digital literacy and environmental awareness—emerges as a key factor in fostering community-based innovation. Therefore, this study highlights the importance of intergenerational collaboration in supporting the achievement of Sustainable Development Goal (SDG) 12 on responsible consumption and production.